ANALISIS PLACE BRANDING UNTUK MENINGKATKAN CITRA KABUPATEN PURWAKARTA SERTA IMPLIKASINYA TERHADAP KEPUTUSAN MENGUNJUNGI DESTINASI PARIWISATA: Survei terhadap Wisatawan Nusantara yang Berkunjung ke Kabupaten Purwakarta - Wulandari, Tresna (2012)
Tourists have central role as decision maker to visit certain tourism destination.However the number of visitation to every tourism destination relatively fluctuatif. That's presumable by poor image of Purwakarta as tourism destination. Place branding is a strategy to enhance the image of Purwakarta, not only as industrial area, but at the same time as tourism destination. The purpose of this study is to determine: 1) the description of place branding; 2) the description of city's image; 3) tourist' decision to visit; 4) the influence of place branding into into the tourists' decision to visit the tourism destination; 5) the influence of city's image into the tourists' decision to visit the tourism destination; 6) the influence place branding into city's image; 7) the influence of place branding and city's image into tourists' decision to visit the tourism destination simultanously. The object of the research is local tourists who visits 11 of tourism destination in Purwakarta. The research's method is descriptive verifikatif. Data source utilized is primary and secondaries one. From the population of 134.717, taken the number of research sample as many as 100 local tourists. Researcher selects probability sampling, especially cluster one as sampling technique. Data collecting technique through the interview, observation, questionaire, and literatur study. This study aims to determine the effect of place branding to enhance the city's image and the implications for tourists' decision to visit. Processing data using path analysis with the SPSS 19 software applications. The results showed that implementation of place branding assessed good enough by local tourists. The image of Purwakarta assessed very high. The tourists' decision to visit assessed high. The level of influence place branding into tourists' decision to visit tourism destination is 7,18% or 0,268 (low). The level of influence image into tourists' decision to visit tourism destination is 18,06% or 0,425 (strong enough). The level of influence place branding into city's image is 43,69% or 0,661 (strong). The level of influence place branding and city's image into tourists' decision to visit tourism destination simultanously 40,3% or 0,403 (strong enough). Therefore, Purwakarta needs to provide and develop facilities evenly accross tourist destination, including public transport. Promoting the component of marketing campaign (slogan and logo of Purwakarta) continously and holding innovative events and sponsorship. Also strengthen coordination accross department and stakeholder partnership through the various tourism fairs to promote tourism of Purwakarta